Authorship Pattern In History Literature Cited In Doctoral Dissertations Accepted By Kurukshetra University and Punjab University: an Analysis: Exploring Authorship Patterns and Collaboration in History Literature: A Comparative Analysis of Kurukshetra University and Punjab University Doctoral Dissertations (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Studies theauthorship pattern and collaborative research in history, based on the datacollected from doctoral dissertations accepted by Kurukshetra University andPunjab University from 1998-2007.The study revealed that the collaborativeresearch is more favored than the solo research. The authorship collaborationis more in Journal articles than in books. The study concluded that authorshippattern, the degree of collaboration and the average number of authors weredifferent in journals and in books.